Prognostic significance of PD‐L2 expression in patients with oral squamous cell carcinoma—A comparison to the PD‐L1 expression profile - Manuel Weber; Falk Wehrhan; Christoph Baran; Abbas Agaimy; Maike Büttner‐Herold; Marco Kesting; Jutta Ries (Cancer Medicine)
Abstract Background Despite the observed association of increased PD‐L1 expression in peripheral blood of oral squamous cell carcinoma (OSCC) patients with histomorphologic parameters, the role of the PD1 ligands—PD‐L1 and PD‐L2—is insufficiently understood. Aim of the study was to investigate whether the alterations of PD‐L1 and PD‐L2 expression in blood are associated with survival and could serve as immune monitoring parameter. Moreover, it should be analyzed if PD‐L2 is differentially expressed in tissue and blood samples of OSCC patients compared to healthy controls and if there is an association of PD‐L2 expression with histomorphologic and prognostic tumor parameters. Methods PD‐L2 mRNA expression was analyzed in tumors and healthy oral mucosa specimens and in corresponding peripheral blood samples of 48 OSCC patients and 26 healthy controls using RT‐qPCR. A cutoff point (COP) was determined and a chi‐square test (χ2 test) was carried out. Survival analysis of PD‐L2 and previously reported PD‐L1 expression data was performed using Kaplan‐Meier analysis (Log‐rank test). Results PD‐L2 expression in tissue samples was significantly (P < 0.001) higher in OSCC patients compared to healthy controls. A significant association of PD‐L2 expression above the COP (positive) with malignancy was ascertained (P < 0.001). A significant (P = 0.01) association of previously reported PD‐L1 expression rates in peripheral blood with survival could be shown. Conclusion Peripheral blood PD‐L1 expression might be a prognostic marker for OSCC patients and a possible parameter to monitor immune dysfunction in malign diseases. In the peripheral blood, PD‐L1 might be more relevant for immune tolerance than PD‐L2. Local PD‐L2 expression in tissue samples might be useful as a diagnostic parameter for malignancy and could contribute to the immunosuppressive local microenvironment in OSCC.